Pelatihan Penulisan Artikel Ilmiah Penelitian Tindakan Kelas Berbasis AI untuk Meningkatkan Kemampuan Mahasiswa Baru dalam Publikasi Ilmiah - Hakim, Nur; Buang, Nursahar; Novelti, Novelti; Hanim, Siti Aisyah; Soleman, Soleman (Universitas Pahlawan Tuanku Tambusai, 2025)
The Student Creativity Program (PKM) aims to train teachers in writing scientific articles on Classroom Action Research (CAR) based on Artificial Intelligence (AI) through intensive training. The research method used is descriptive qualitative with a participatory approach, where participants (teachers) are given workshops, mentoring, and direct practice using AI tools such as ChatGPT, Grammarly, and Turnitin for data analysis, article preparation, and plagiarism checking. The results of the study showed a significant increase in teachers' ability to write CAR articles, with 85% of participants successfully compiling article drafts that met scientific standards, and increasing writing time efficiency by up to 40% thanks to the use of AI. This training not only improves digital teacher literacy but also opens up opportunities for innovation in technology-based educational research.